2017
DOI: 10.1002/da.22616
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-brief behavioral skills trainings for blood injection injury phobia

Abstract: Brief, video-based instructions in muscle tension and normocapnic breathing are effective in reducing BII symptom severity and require minimal time and expertise. HRT may be particularly helpful in reducing fainting caused by cerebral vasoconstriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Treatments proved effective, also when administered in a one-session format ( Öst et al, 1992 ). A recent study ( Meuret et al, 2017 ) demonstrated that even very brief (12 min) video-based instructions of applied tension or a hypoventilation breathing techniques led to substantial reductions of subjective and bodily-symptoms during exposure to BII-relevant stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments proved effective, also when administered in a one-session format ( Öst et al, 1992 ). A recent study ( Meuret et al, 2017 ) demonstrated that even very brief (12 min) video-based instructions of applied tension or a hypoventilation breathing techniques led to substantial reductions of subjective and bodily-symptoms during exposure to BII-relevant stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The most notable feature of the results was the usefulness of RESP in reducing vasovagal symptoms in blood donors. Previous research has noted the potential value of “anti‐hyperventilation” techniques for blood‐injury‐injection (BII) phobics, people with especially strong fears of blood and needles . However, this is the first use of this approach in a more general, non‐BII population.…”
Section: Discussionmentioning
confidence: 92%
“…Nevetheless, it might not require much more training to observe positive effects in higher‐fear individuals. Meuret et al recently found that it was possible to impact the reactions of individuals with BII phobia to strong stimuli (e.g., a video depicting portions of open heart surgery) with 12 minutes of Hypoventilation Respiratory Training. Although longer than the videos used in the present study, this is quite brief in comparison to typical behavior therapy and had effects on people with much stronger fears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review also yielded a study that investigated relaxation in the treatment of blood-injection-injury phobias. Meuret et al 41 compared the efficacies of Symptom Associated Tension (SAT) Training and Hypoventilation Respiratory Training (HRT) with that of Relaxation Skills Training (RST) in treating blood-injection-injury phobias. These were delivered via 12-minute video-guided trainings.…”
Section: Others (N = 9)mentioning
confidence: 99%